2022
DOI: 10.2217/bmm-2022-0160
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Levels of Ferritin May Predict Poor Survival and Walking Ability for Patients with Hip Fractures: A Propensity Score Matching Study

Abstract: Aim: To identify the relationship between ferritin and outcomes for patients with hip fractures. Patients & methods: All patients with hip fractures presenting between May 2017 and January 2021 were included. Univariate and multivariate analyses were performed to determine the risk factors for 1-year survival. Propensity score matching (PSM) was performed for groups divided by ferritin levels. Results: A total of 165 patients were included of whom 28 died during the first year after surgery. Ferritin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Many studies based on populations have suggested that patients with hip fractures treated with anti-osteoporosis medications may face an improved prognosis after surgery ( 29 , 30 ). However, many risk factors were also reported to be associated with the risk and prognosis of geriatric hip fractures, such as supplementation of vitamin D3 ( 31 ), the neutrophil-to-lymphocyte ratio ( 32 ), ferritin ( 33 ), and so on. Sarcopenia as an age-related and complex disease had attracted much attention in recent years ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies based on populations have suggested that patients with hip fractures treated with anti-osteoporosis medications may face an improved prognosis after surgery ( 29 , 30 ). However, many risk factors were also reported to be associated with the risk and prognosis of geriatric hip fractures, such as supplementation of vitamin D3 ( 31 ), the neutrophil-to-lymphocyte ratio ( 32 ), ferritin ( 33 ), and so on. Sarcopenia as an age-related and complex disease had attracted much attention in recent years ( 34 ).…”
Section: Discussionmentioning
confidence: 99%